Acute Respiratory Illnesses in Children in the SARS-CoV-2 Pandemic: Prospective Multicenter Study - Haddadin, Zaid; Schuster, Jennifer E.; Spieker, Andrew J.; Rahman, Herdi; Blozinski, Anna; Stewart, Laura; Campbell, Angela P.; Lively, Joana Y.; Michaels, Marian G.; Williams, John V.; Boom, Julie A.; Sahni, Leila C.; et al. (Pediatrics (Evanston), 2021)
Nonpharmaceutical interventions against coronavirus disease 2019 likely have a role in decreasing viral acute respiratory illnesses (ARIs). We aimed to assess the frequency of respiratory syncytial virus (RSV) and influenza ARIs before and during the coronavirus disease 2019 pandemic. This study was a prospective, multicenter, population-based ARI surveillance, including children seen in the emergency departments and inpatient settings in 7 US cities for ARI. Respiratory samples were collected and evaluated by molecular testing. Generalized linear mixed-effects models were used to evaluate the association between community mitigation and number of eligible and proportion of RSV and influenza cases. Overall, 45 759 children were eligible; 25 415 were enrolled and tested; 25% and 14% were RSV-positive and influenza-positive, respectively. In 2020, we noted a decrease in eligible and enrolled ARI subjects after community mitigation measures were introduced, with no RSV or influenza detection from April 5, 2020, to April 30, 2020. Compared with 2016-2019, there was an average of 10.6 fewer eligible ARI cases per week per site and 63.9% and 45.8% lower odds of patients testing positive for RSV and influenza, respectively, during the 2020 community mitigation period. In all sites except Seattle, the proportions of positive tests for RSV and influenza in the 2020 community mitigation period were lower than predicted. Between March and April 2020, rapid declines in ARI cases and the proportions of RSV and influenza in children were consistently noted across 7 US cities, which could be attributable to community mitigation measures against severe acute respiratory syndrome coronavirus 2.